2020
DOI: 10.1101/2020.11.02.360941
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neighboring colonies influence uptake of thermotolerant endosymbionts in threatened Caribbean coral recruits

Abstract: Intervention strategies to enhance coral resilience include manipulating the association between corals and their algal endosymbionts. While hosting thermotolerant Durusdinium trenchii can increase bleaching thresholds in adults, its effects remain largely unknown during the early life stages of Caribbean corals. Here, we tested if Orbicella faveolata recruits could establish symbiosis with D. trenchii supplied by nearby “donor” colonies and examined the resulting ecological trade-offs to evaluate early Symbio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…Our results suggest that the adult hosts at the site might not be the major source of symbionts, which is similar to other studies where the predominant symbionts in surrounding corals and other cnidarian hosts often differed from those found in nearby recruits (Abrego et al, 2009b; Ali et al, 2019; Andras et al, 2011; Chan et al, 2019; Gómez‐Cabrera et al, 2008; Little et al, 2004; Mellas et al, 2014; Poland et al, 2013; Thornhill, Daniel, et al, 2006; Thornhill, LaJeunesse, et al, 2006; Yamashita et al, 2013). Even in lab settings, where coral colonies are seemingly the only source of symbionts, recruits can harbor symbiont types that differ from the adult source colony (Ali et al, 2019; Williamson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that the adult hosts at the site might not be the major source of symbionts, which is similar to other studies where the predominant symbionts in surrounding corals and other cnidarian hosts often differed from those found in nearby recruits (Abrego et al, 2009b; Ali et al, 2019; Andras et al, 2011; Chan et al, 2019; Gómez‐Cabrera et al, 2008; Little et al, 2004; Mellas et al, 2014; Poland et al, 2013; Thornhill, Daniel, et al, 2006; Thornhill, LaJeunesse, et al, 2006; Yamashita et al, 2013). Even in lab settings, where coral colonies are seemingly the only source of symbionts, recruits can harbor symbiont types that differ from the adult source colony (Ali et al, 2019; Williamson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Symbiodiniaceae are released into the reef environment by adult corals (Koike et al, 2007; Muscatine & Pool, 1979; Stimson & Kinzie, 1991) and have been recovered from the water column, macroalgae, and sediments (e.g., Adams et al, 2009; Coffroth et al, 2006; Littman et al, 2008; Manning & Gates, 2008; Porto et al, 2008; Takabayashi et al, 2012). Numerous studies have demonstrated that newly settled recruits do acquire symbionts from the water column, sediments and, in lab settings, from nearby coral colonies (Ali et al, 2019; Coffroth et al, 2006; Cumbo et al, 2013; Nitschke et al, 2015; Quigley et al, 2019; Sweet, 2014; Williamson et al, 2021). Since outplant‐site adults and recruits are on the same reef and thus in similar environments, we might predict that the symbionts within these two life stages would be similar.…”
Section: Discussionmentioning
confidence: 99%
“…If a specific taxon (i.e. Breviolum) is implicated in SCTLD infection, managers may choose to provide recruits with sources of alternative taxa during initial symbiosis establishment (Williamson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…labyrinthiformis recruits to serve as symbiont sources (Williamson et al, 2021) trenchii, and one hosted Breviolum only.…”
Section: Recruit Developmentmentioning
confidence: 99%